1995
DOI: 10.1074/jbc.270.42.25244
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12-O-Tetradecanoylphorbol-13-acetate on Estrogen Receptor Activity in MCF-7 Cells

Abstract: The effects of long term treatment with 12-O-tetradecanoylphorbol-13-acetate (TPA) on estrogen receptor (ER) expression in the human breast cancer cell line, MCF-7, were studied. This study demonstrates that treatment of cells with the phorbol ester blocked estrogen receptor activity. Treatment of cells with 100 nM TPA resulted in an 80% decrease in the level of ER protein and a parallel decrease in ER mRNA and binding capacity. Following removal of TPA from the medium, the level of ER protein and mRNA returne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…A first hint on the interaction between PKCd and ERa came from the downregulation of both proteins observed after treatment of ERa-positive breast cancer cells with TPA and estradiol, which was in line with reports on the downregulation of PKCd by TPA and estrogen (Gschwendt, 1999;Shanmugam et al, 1999). Other authors reported that long-term treatment of MCF-7 cells with TPA resulted in a block of ERa activity (Martin et al, 1995) or a decrease of ERa protein, ERa mRNA and DNA binding capacity (Saceda et al, 1991). These findings suggested a crosstalk between PKCd and ERa functions, and we hypothesized that PKCd signalling may be related to ERa activation.…”
Section: Discussionsupporting
confidence: 75%
“…A first hint on the interaction between PKCd and ERa came from the downregulation of both proteins observed after treatment of ERa-positive breast cancer cells with TPA and estradiol, which was in line with reports on the downregulation of PKCd by TPA and estrogen (Gschwendt, 1999;Shanmugam et al, 1999). Other authors reported that long-term treatment of MCF-7 cells with TPA resulted in a block of ERa activity (Martin et al, 1995) or a decrease of ERa protein, ERa mRNA and DNA binding capacity (Saceda et al, 1991). These findings suggested a crosstalk between PKCd and ERa functions, and we hypothesized that PKCd signalling may be related to ERa activation.…”
Section: Discussionsupporting
confidence: 75%
“…4A-D). The effect of TPA on estrogen receptor gene activation is cell and promoter specific, and probably requires the synthesis or activation of a factor(s) following stimulation (Cho & Katzenellenbogen 1993, Martin et al 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that activation of growth factor signaling might indeed reduce ERa expression and/or function. For example, treatment with EGF, IGF-I, TGFb or phorbol myristate acetate (TPA) reduces the levels of ERa mRNA and protein in MCF-7 cells (Martin et al 1995, Stoica et al 1997, 2000a. Increased signaling through EGFR, PI3K/AKT, PKA and PKC is involved in this phenomenon.…”
Section: Growth Factor Signaling In Resistance To Endocrine Therapymentioning
confidence: 99%